2010
DOI: 10.1037/a0019998
|View full text |Cite
|
Sign up to set email alerts
|

Loss of cognitive skill across delays: Constraints for theories of cognitive skill acquisition.

Abstract: Mastering a cognitive skill requires many practice sessions, occurring over a period of days, weeks, months, or even years. Although a large body of research describes and explains gains made within a given practice session, few studies have investigated what happens to these gains across a delay, and none have examined effects of delays on item-general gains. Across 3 experiments, participants performed alphabet arithmetic verification in an initial practice session followed by a test session after a delay (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 36 publications
1
22
1
Order By: Relevance
“…The transfer to memory-based processing has been extensively studied in the automaticity literature, with questions ranging from whether transfer to retrieval is a gradual or abrupt process (Rickard, 1997;Touron, 2006) to what information is encoded for later retrieval during skill acquisition (Lassaline & Logan, 1993;Logan & Etherton, 1994) to the retention of memory-based processing after practice (Grant & Logan, 1993;Wilkins & Rawson, 2010). In contrast, the extent to which participants can control transfer to retrieval has been less well examined.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The transfer to memory-based processing has been extensively studied in the automaticity literature, with questions ranging from whether transfer to retrieval is a gradual or abrupt process (Rickard, 1997;Touron, 2006) to what information is encoded for later retrieval during skill acquisition (Lassaline & Logan, 1993;Logan & Etherton, 1994) to the retention of memory-based processing after practice (Grant & Logan, 1993;Wilkins & Rawson, 2010). In contrast, the extent to which participants can control transfer to retrieval has been less well examined.…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, a voluminous amount of research has shown speed and accuracy gains with practice in many different cognitive tasks and with a diversity of learners (e.g., Anderson, Fincham, & Douglass, 1999;Logan, 1988;McAndrews & Moscovitch, 1990;Rawson, 2004;Rawson & Middleton, 2009;Rawson & Touron, 2009;Schneider & Shiffrin, 1977;Touron & Hertzog, 2004;Touron, Swaim, & Hertzog, 2007;Wilkins & Rawson, 2010). According to memory-based processing (MBP) theories of automaticity (e.g., Logan, 1988;Palmeri, 1997;Rickard, 1997), improvements in speed during practice are due to a shift from an item-general algorithmic process to an item-specific memory-based process.…”
Section: Introductionmentioning
confidence: 98%
“…Other research has demonstrated that both younger and older adults show fluency gains when rereading lengthy passages, although they differ somewhat in the level of processing showing facilitation (e.g., Stine-Morrow, Gagne, Morrow, & DeWall, 2004). However, these and other rereading methodologies (for a review, see Collins & Levy, 2008) do not pin down the involvement of memory-based processing per se, given that fluency gains may also reflect improvement in the efficiency of algorithmic processes (e.g., Wilkins & Rawson, 2010). Given that Rawson and Touron (2009) report the only direct evidence for relatively preserved memory-based automaticity in older adults, one goal of the current research was to replicate these initial findings (for recent emphasis on the importance of replicating novel findings, see Pashler & Harris, 2012;Roediger, 2012;Schmidt, 2009).…”
Section: Age Differences In Memory-based Automaticitymentioning
confidence: 99%
“…The contribution of memory-based processing to speed-ups with practice has been shown in a wide range of skill acquisition tasks, including alphabet arithmetic (e.g., Klapp, Boches, Trabert, & Logan, 1991;Wilkins & Rawson, 2010, pound arithmetic (described below; e.g., Rickard, 1997;Touron et al, 2004), multiplication (e.g., Rickard, Lau, & Pashler, 2008), visual search (e.g., Fisk, Hertzog, Lee, Rogers, & Anderson-Garlach, 1994), noun-pair look-up (e.g., Rogers et al, 2000;Touron & Hertzog, 2004a), lexical decision (e.g., Grant & Logan, 1993;Logan, 1988), and numerosity judgments (e.g., Jenkins & Hoyer, 2000;Lassaline & Logan, 1993;Palmeri, 1997). Most relevant for present purposes, recent research has also established the contribution of memory-based processing to speed-ups with practice in syntactic and semantic processes during reading tasks (Rawson, 2004(Rawson, , 2010Rawson & Middleton, 2009;Rawson & Touron, 2009).…”
Section: Early Theories Of Automaticity Involved Whatmentioning
confidence: 99%
“…The senior level courses considered in this study rely to varying degrees on prior knowledge gained in the accounting program. Therefore, course sequencing that leaves more time between courses could be associated with lower performance in the senior level courses (Wilkins & Rawson, 2010).…”
Section: Introductionmentioning
confidence: 99%